Application of the brg.lifemod for simulations of step-movements and kicks and estimation of joint stress - Witte, K.; Jackstien, M. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
The purpose of this study was to evaluate a multi body system (BRG.LifeMod) in regard to the application for several simple movements: step-up, kicking movements, step movements. Results of other authors maintain the simulation results. The presented models help to estimate the stress in joints of the lower extremities